Novel plant inputs influencing Ralstonia solanacearum during infection - Zuluaga Cruz, A. Paola; Puigvert, Marina; Valls, Marc (Frontiers in Microbiology, 2013)
Ralstonia solanacearum is a soil and water-borne pathogen that can infect a wide range of plants and cause the devastating bacterial wilt disease. To successfully colonize a host, R. solanacearum requires the type III secretion system (T3SS), which delivers bacterial effector proteins inside the plant cells. HrpG is a central transcriptional regulator that drives the expression of the T3SS and other virulence determinants. hrpG transcription is highly induced upon plant cell contact and its product is also post-transcriptionally activated by metabolic signals present when bacteria are grown in minimal medium. Here, we describe a transcriptional induction of hrpG at early stages of bacterial co-culture with plant cells that caused overexpression of the downstream T3SS effector genes. This induction was maintained in a strain devoid of prhA, the outer membrane receptor that senses bacterial contact with plant cells, demonstrating that this is a response to an unknown signal. Induction was unaffected after disruption of the known R. solanacearum pathogenicity regulators, indicating that it is controlled by a non-described system. Moreover, plant contact-independent signals are also important in planta, as shown by the hrpG induction triggered by apoplastic and xylem extracts. We also found that none of the amino acids or sugars present in the apoplast and xylem saps studied correlated with hrpG induction. This suggests that a small molecule or an environmental condition is responsible for the T3SS gene expression inside the plants. Our results also highlight the abundance and diversity of possible carbon, nitrogen and energy sources likely used by R. solanacearum during growth in planta.